Análise do aconselhamento em HIV/AIDS: reflexões à luz de Paulo Freire - Miranda, Karla Corrêa Lima (2004)
The infection for the HIV/AIDS configures a public heath problem and has brought complex matters and prejudices. The counselling is a theorical and methodological strategy will give support to the professionals to work problems. The counselling is a moment that the professional could be help for the person to underestand and to perform the reality. In this case, the study has an objective to investigate the strategies used by in health professionals to do the counselling. These study is a qualitative research, inspered in Freire's theory. We used the content analysis of Bardin to work with the records. To the group, the counselling is divided at the three moments: to think the counselling, to do the counselling and to feel the couselling. The focus of the counsellig is the inforrmation, the main dificulties are the institution na the clients, and the facility is the team, that have a good relationship. The counsellig is a special moment, but doen't in educational activity. We suggest a methodology in counsellig, using the Freire's concepts.